Understanding Physical Exercises and Aging as Factors in Adult Learning - Olojede, Adeshina Abideen; Ononaiwu, Agnes Ijeoma; Ayyba, Usman Katako; Eziafa, Izamah Rita (European Scientific Journal, ESJ, 2023)
This paper examined the erroneous belief that learning in adulthood would add little or no value to the society; suggesting that, adultsâ€™ learning is perceived from the vantage point of approximately how much time is left to live. The advancement in health technology and nutrition, human survival and most especially as growth in age is increasing; promoting learning in adulthood could not be seen as a wasted effort. Various studies and researches have established the usefulness of regular exercise as an avenue to reduce fatigue and loss of memory as well as how aging affect adulthood, but none has been tested on its effectiveness on adult learning. The population of the study involves of all the adults learners estimated to be one thousand, four hundred and seventy-nine (1,479) from the three Zones in Niger State out of which a sample size of two hundred and twenty-five randomly was picked for the study. The instruments used for the study were empirical facts through literature review, observations, interviews (for learners) and questionnaires (for facilitators). The ten (10) items questionnaire was tagged â€œPhysical Exercises and Aging as Factors of Adult Learning (PEAFAL)â€. It was a 4 point rating scale questionnaire with a reliability value of 0.89 obtained through the Pearson Moment Product Coefficient method after test re-tests of the instrument. Data collected were collated and analysed using descriptive and inferential statistical methods respectively while the hypotheses were tested at 0.05 alpha level of significance. The study showed that physical exercises can adequately influence active participation of learners in learning if use appropriately through positive impact in the following order: backyard gardening (Î² = 0.41; p < 0.05), running (Î² = 0.34; p < 0.05), dancing (Î² = 0.30; p < 0.05), farming (Î² = 0.27; p < 0.05), walking (Î² = 0.25; p < 0.05), swimming (Î² = 0.21; p < 0.05). The study also revealed that there was significant difference in the interest and participation of old and young adults (Cal-t = 2.820, Crit-t = 1.96, df = 1308, P < .05 level of significance. The paper therefore emphatically established the relevant of exercise and aging and their roles in promoting adult learning. It concludes that regular exercises can improve stiffness in adult and enhance memory as adult ages. The paper therefore recommended that physical and health issues be emphasised in non-formal education curriculum and adult facilitators should imbibe the culture of regular exercises among learners especially among those of age.